A redução na disponibilidade de recursos florais aumenta o tempo de forrageamento de abelhas sem ferrão (Melipona subnitida, Apidae, Meliponini) - Pereira, Jaciara da Silva (2017)
The abundance of flowering plants around the nests shapes the nest-internal and nest-external activities of social bee colonies. In addition to limiting the quantity of resources collected, the availability of floral resources in the environment may influence the distance that foragers have to fly in order to collect food. With decreasing abundance of flowering plants, bees more likely visit distant resources and, consequently, increase their flight range in search for new food sources. The semiarid region in north-eastern Brazil, the Caatinga, is characterized through a short rainy season with a high availability of floral resources on the one hand, and, on the other hand, through an extended dry season during which only few tree species are in bloom. In face of this striking difference concerning the availability of floral resources in the course of the year in this region, the aim of the present study was to assess the time that foragers of Melipona subnitida (Apidae, Meliponini) need to collect food (nectar and pollen) during times of high and low abundance of flowering plants. We investigated the time spent by foragers to collect floral resources in three distinct landscapes of the Brazilian north-east: an urban area and an area with natural caatinga vegetation, both at Mossoró/RN, as well as a high-altitude humid forest enclave at Martins/RN. During the study (July of 2015 to August of 2016), we counted monthly the number of plant species in bloom in each study location. During one day in each month, we measured at each study location the foraging times of bees, marked previously for individual identification, from three colonies of M. subnitida, marking the exit and return times between 05h00 and 08h00. Additionally, we identified the respective resource collected (nectar or pollen) and determined the plant species visited by the individuals through analysis of their corbicula pollen loads or the pollen on their bodies. Our results indicate that the quantity of plant species around the nests had an impact on the time the bees spent for food collection. With decreasing availability of floral resources, the bees spent more time foraging. This implies a greater energy expenditure for bee in the absence of resources near the nest and bee will have to move to distant areas